DAXplus family: Ein Aktienindex zur Darstellung der Performance von Familienunternehmen; DAXplus Family – Primer on a family firm stock index in Germany - Ann-Kristin Achleitner; Christoph Kaserer; Tobias Kauf; Sarah Volk (Technische Universität München, Center for Entrepreneurial and Financial Studies (CEFS), 2010)
In January 2010 the Deutsche Börse Group introduced two family firm stock indices. Both indices are calculated as price and performance indices and extend the number of investment strategy indices of Deutsche Börse Group. The DAXplus Family is an all-share index whereas the DAXplus Family 30 represents a selection index of the 30 largest and most liquid Prime Standard family firms of Frankfurt Stock Exchange (FSE). The index development traces back to a mutual research project between Deutsche Börse Group and Technische Universität München (TUM). In order to be applicable for DAXplus Family index inclusion, a firm has to fulfil a founding family definition: the founder(s) and/or related family members have to control at least 25% of voting rights or at least 5% voting rights if the founder or the family is not only shareholder but also active management or supervisory board member. Out of 123 family firms that were included in the DAXplus Family at index introduction in January 2010, about 95% (117 firms) qualified with both elements of the definition - required control of voting rights and board representation. Only 23% of the index firms are characterised by blockholdings of the family below 25%. The DAXplus Family 30 has a correlation of 99.6% with the all-share index DAXplus Family and a correlation of 83.6% with the German blue chip index DAX. A performance backtesting of the DAXplus Family 30 from June 2002 to July 2010 revealed an annualized return of 11.5% at an annualized volatility of 24%. Further details about the indices' theoretical and empirical foundation, underlying concept, main features as well as descriptive characteristics are presented in this primer.
Keywords: G11; G32; G34; 330; Family Firm; Style Index; Ownership Structure; Corporate Governance; Aktienindex; Corporate Governance; Eigentümerstruktur; Familienunternehmen; Deutschland